PERAN PEMERINTAH DESA DALAM PEMBANGUNAN INFRASTRUKTUR DI DESA MUARA BARU - Cahyani, Elista Nanda; Safitri, Maudy; Handayani, Putri Rizki; Apridheo, Paskasius (Faculty of Social and Political Sciences, Universitas Swadaya Gunung Jati, 2023)
This research aims to find out the role of the village government and the participation of the Muara Baru Village community in infrastructure development. This research uses a library study type of research with data collection techniques through journals, books, and literature articles. The results of this research are that the community and village government are both less than optimal in infrastructure development, due to lack of funds and community participation in infrastructure development.